WORKPLACE DIGITALIZATION AND ITS EFFECTS ON HUMAN RESOURCE MANAGEMENT PRACTICES - Sridesyani Munawaroh; Samudra Syarif Wahyu Hidayatullah; Asep Ferry Rachmat; Kasmin (CV. Adiba Aisha Amira, 2025)
The digitalization of workplaces has revolutionized Human Resource Management (HRM) by integrating advanced technologies such as artificial intelligence (AI), cloud computing, big data, and the Internet of Things (IoT). These technologies have significantly improved operational efficiency, automated administrative tasks, and enabled data-driven decision-making. This study explores the transformative impact of digitalization on HRM practices, focusing on talent acquisition, employee training, performance management, and workplace culture. A mixed-methods approach is employed, combining qualitative and quantitative methodologies. The qualitative aspect includes a literature review and in-depth interviews with HR professionals, while the quantitative component consists of a survey targeting HR practitioners across various industries. The findings highlight how AI-driven recruitment processes, cloud-based HR systems, and digital training tools have optimized HR functions. Additionally, real-time performance analytics and virtual collaboration platforms have enhanced employee engagement and productivity. The study concludes that while digitalization enhances HRM efficiency and workforce adaptability, addressing its ethical, legal, and technical challenges is imperative. Future research should explore the long-term effects of digital HRM on employee well-being, retention, and overall organizational performance. The findings contribute to both academic research and practical HR strategies, offering insights into navigating digital transformation in workforce management effectively.